L’importance politique et stratégique de l’Arctique : une perspective canadienne - Halstead, John (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1989)
The Arctic lends a special dimension to Canadian foreign and defence policies because it is the most harsh and the least populated part of Canada, it is where American security interests impinge most insistently and it is the ham in the superpower sandwich. Moreover, the Arctic is being drawn increasingly into the international System, with important policy implications: Canada cannot expect to develop effective policies to deal with its own Arctic in isolation from other countries; and Canada's ability to carry such policies out will depend on the extent to which it can exercise effective control over its vast territory. These implications are of particular importance to Canada's relations with the United States, with whom we must strike a balance between the advantages of cooperation and the need to protect Canadian interests. This task promises to become more complex as the forward air and sea defence of the United States pushes further north, while the move toward space-based warning and surveillance Systems reduces American reliance on Canadian territory and Canadian access to American information. Traditionally Canada has dealt bilaterally with the United States on such matters but the time has come to supplement the bilateral channels with multilateral approaches wherever possible, in order to emphasize the point that the defence of North America is an integral part of the defence of the North Atlantic Treaty area. In accordance with this concept, various measures should be considered to reinforce the strategic unity of NATO, to ensure that defence measures in the Arctic are consistent with strategic stability and with arms control policies, and to establish in the Arctic a regime of mutual security, bolstered by a concerted program of circumpolar cooperation.